The Gender Dimension of Intergenerational Transfers in Europe - Bernhard Hammer; Sonja Spitzer; Lili Vargha; Tanja Istenič (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2019)
This paper analyses the gender dimension of intergenerational transfers in European countries using National Transfer Accounts data on age- and gender-specific transfers in 2010. We combine data on public and private transfers with demographic information to estimate gender-specific net transfer benefits by life stage and over the whole life course. Furthermore, public old-age benefits are decomposed into yearly averages as well as the number of years that individuals can expect to be net recipients of public transfers. The results show remarkable differences between genders, especially in old age. Yearly net public benefits in old age are considerably smaller for women. However, the total public benefits over the whole retirement period are higher for women due to their higher life expectancy.
Keywords: 300; Gender inequalities; intergenerational transfers; National Transfer Accounts; unpaid work